Zionist Ideology and the Translation of Hebrew - Green, Jeffrey (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractZionist Ideology and the Translation of Hebrew — Thelanguage used by the author of a text may be of ideological significance, and this is a feature that may be lost in translation. As with many languages associated with relatively small, emergent nationalities, the choice to write in modern Hebrew may be related to a nationalist ideology, in this case, Zionism. This article maintains that the creation of Hebrew is similar to the creation of other minority languages, whose use is restricted to a relatively small population of native speakers, as opposed to world languages, widely known and used by people of many countries. The development and use of a minority language is an expression of self-assertion that entails a degree of isolation. This article examines a novel by a contemporary Israeli novelist, Aharon Megged, and explores the ideological significance of its being written in Hebrew as a literary feature of the novel. It notes the aspects of that ideological significance that would be lost in translation and suggests that translators should be aware of this issue.